2003
DOI: 10.1089/089277903321618699
|View full text |Cite
|
Sign up to set email alerts
|

Is Telesurgery a New Reality? Our Experience with Laparoscopic and Percutaneous Procedures

Abstract: Background: Minimally invasive surgery offers many advantages, but its correct practice is associated with a steep learning curve. Telesurgery allows a surgeon at a remote site to guide and teach surgeons at a primary site by utilizing robotic devices, telecommunications, and video technology, thereby reducing complications.Patients and Methods: From September 1998 to July 2000, 17 procedures were telementored between two sites 9230 km apart: a primary operating room at the Policlinico Casilino "Tor Vergata" U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 26 publications
1
39
0
1
Order By: Relevance
“…In a study involving transcontinental telementoring, 5/17 of cases failed to achieve site-to-site connection, which was attributed to international telephone line overload (13). The use of protected private networks permitted completion of 100% of our complex operative tasks in our experiments.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study involving transcontinental telementoring, 5/17 of cases failed to achieve site-to-site connection, which was attributed to international telephone line overload (13). The use of protected private networks permitted completion of 100% of our complex operative tasks in our experiments.…”
Section: Discussionmentioning
confidence: 83%
“…Other investigators using ISDN found that network traffic severely limited their ability to perform simpler tasks involving telementoring and adjustment of laparoscope positioning (13). In a study involving transcontinental telementoring, 5/17 of cases failed to achieve site-to-site connection, which was attributed to international telephone line overload (13).…”
Section: Discussionmentioning
confidence: 99%
“…The remote surgeon controlled the laparoscope via an Automated Endoscopic System for Optimal Positioning (AESOP 3000, Intuitive Surgical, Inc., Sunnyvale, CA). This group has now carried out telesurgical telementoring in more than 17 cases using AESOP or the Percutaneous Access to the Kidney robot (PAKY, Johns Hopkins University, Baltimore, MD) (Bove et al, 2003).…”
Section: Surgical Telemonitoringmentioning
confidence: 99%
“…This technological development gave an impulse to many other telerobotic procedures, allowing the urologists to accomplish even more complex surgeries, such as spermatic vein ligation, renal biopsy, percutaneous renal access, nephrectomy and pyeloplasty (2). Coming along with such worldwide technological advance, the feasibility of telerobotic surgery at our institution was tested and it is herein reported as an original report from our local academic environment.…”
Section: Introductionmentioning
confidence: 99%